Zircon geochronology and geochemistry to constrain the youngest eruption events and magma evolution of the Mid-Miocene ignimbrite flare-up in the Pannonian Basin, eastern central Europe - Lukács, R.; Harangi, S.; Bachmann, O.; Guillong, M.; Danisik, Martin; Buret, Y.; von Quadt, A.; Dunkl, I.; Fodor, L.; Sliwinski, J.; Soós, I.; Szepesi, J. (Springer, 2015)
A silicic ignimbrite flare-up episode occurred in the Pannonian Basin during the Miocene, coeval with the syn-extensional period in the region. It produced important correlation horizons in the regional stratigraphy; however, they lacked precise and accurate geochronology. Here, we used U–Pb (LA-ICP-MS and ID-TIMS) and (U–Th)/He dating of zircons to determine the eruption ages of the youngest stage of this volcanic activity and constrain the longevity of the magma storage in crustal reservoirs. Reliability of the U–Pb data is supported by (U–Th)/He zircon dating and magnetostratigraphic constraints. We distinguish four eruptive phases from 15.9 ± 0.3 to 14.1 ± 0.3 Ma, each of which possibly includes multiple eruptive events. Among these, at least two large volume eruptions (>10 km3) occurred at 14.8 ± 0.3 Ma (Demjén ignimbrite) and 14.1 ± 0.3 Ma (Harsány ignimbrite). The in situ U–Pb zircon dating shows wide age ranges (up to 700 kyr) in most of the crystal-poor pyroclastic units, containing few to no xenocrysts, which implies efficient recycling of antecrysts. We propose that long-lived silicic magma reservoirs, mostly kept as high-crystallinity mushes, have existed in the Pannonian Basin during the 16–14 Ma period. Small but significant differences in zircon, bulk rock and glass shard composition among units suggest the presence of spatially separated reservoirs, sometimes existing contemporaneously. Our results also better constrain the time frame of the main tectonic events that occurred in the Northern Pannonian Basin: We refined the upper temporal boundary (15 Ma) of the youngest counterclockwise block rotation and the beginning of a new deformation phase, which structurally characterized the onset of the youngest volcanic and sedimentary phase.